La pensée magique en Californie : Where I Was From de Joan Didion - Sophie Létourneau (Itinéraires, 2015)
American writer Joan Didion, one of the most proeminent New Journalist, made the Californian dream the main topic of Where I Was From. In this essay, she criticizes the influence of “myths” on the political thought of Californians. Rather than restricting her field of investigation to the public sphere, Joan Didion also examines the story of her family. To convey her research, she borrows both to journalism and memoirs writing: her documentation is based on historical data, government reports, news in brief, literature and arts, but she also draws on family archives, oral history and childhood memories, offering a unique “récit de société” in which politics crosses autobiography. This article shows how Where I Was From aims to demystify the Californian dream through research, reminiscence, and the work of mourning by which the author finaly experiences the end of the “enchantment.”